Bangladesh : Economic Reform Measures and the Poor - Gotur, Padma (Washington, D.C. : International Monetary Fund, 1991)
This paper assesses the impact on the poor of the economic reforms undertaken in Bangladesh under Fund-supported structural adjustment programs. It finds that program-induced changes in production, employment, and incomes have benefitted the poor, while the adverse impact of program-induced price changes has been modest. However, as adjustment efforts are intensified under the current structural adjustment program, more pronounced short-term adverse effects might arise, requiring compensatory measures. The paper reviews special assistance programs for the poor, including those designed to mitigate the potential adverse effects of adjustment, noting that improved targeting would yield sizable fiscal savings that could be used for strengthening social programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet